The Great Woods of Lynn and Other Public Parks of the Town in 1903, Being the 15th Annual Report of the Park Commissioners of Lynn, Massachusetts 81 (1903) - (:unkn) unknown (General Publisher, 1903)
[I]t is forbidden … to discharge or carry firearms, except by members of the police force in the discharge of their duties.
--
Keywords: DISCHARGE